2015
DOI: 10.5194/hessd-12-1599-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Groundwater flow processes and mixing in active volcanic systems: the case of Guadalajara (Mexico)

Abstract: Groundwater chemistry and isotopic data from 40 production wells in the Atemajac and Toluquilla valleys, located in and around the Guadalajara metropolitan area, were determined to develop a conceptual model of groundwater flow processes and mixing. Stable water isotopes (δ 2 H, δ 18 O) were used to trace hydrological processes and tritium ( 3 H) to evaluate the relative contribution of modern water in samples. Multivariate analysis including cluster analysis and principal component analysis were used to eluci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Hydrochemical and isotope tracers provide valuable tools for evaluation of groundwater. It is well recognized that major and minor chemical elements may give an insight into water-rock interactions as well as anthropogenic influences affecting the groundwater system as demonstrated in numerous studies (Hem 1989;Mahlknecht et al 2004;Ledesma-Ruiz et al 2015;Cruz-Fuentes et al 2014;Hernández-Antonio et al 2015;Russak et al 2015), while water isotopes may define groundwater recharge areas, mixing and evaporation sources (Edmunds et al 2003;Horst et al 2007;Jiménez-Martínez and Custodio 2008;Mohammed et al 2014;Gonçalvès et al 2015), and radiocarbon isotopes residence times of old groundwater and its distribution (Fontes and Garnier 1979;Clark and Fritz 1997;Edmunds and Smedley 2000;Mahlknecht et al 2006a). More recently, it has been demonstrated that chlorofluorocarbons are useful in evaluating residence times of modern groundwater, mixing patterns and aquifer's vulnerability to contamination (Busenberg and Plummer 1992;Cook et al 1995;Goody et al 2006;Mahlknecht et al 2006b;Horst et al 2008;Darling et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrochemical and isotope tracers provide valuable tools for evaluation of groundwater. It is well recognized that major and minor chemical elements may give an insight into water-rock interactions as well as anthropogenic influences affecting the groundwater system as demonstrated in numerous studies (Hem 1989;Mahlknecht et al 2004;Ledesma-Ruiz et al 2015;Cruz-Fuentes et al 2014;Hernández-Antonio et al 2015;Russak et al 2015), while water isotopes may define groundwater recharge areas, mixing and evaporation sources (Edmunds et al 2003;Horst et al 2007;Jiménez-Martínez and Custodio 2008;Mohammed et al 2014;Gonçalvès et al 2015), and radiocarbon isotopes residence times of old groundwater and its distribution (Fontes and Garnier 1979;Clark and Fritz 1997;Edmunds and Smedley 2000;Mahlknecht et al 2006a). More recently, it has been demonstrated that chlorofluorocarbons are useful in evaluating residence times of modern groundwater, mixing patterns and aquifer's vulnerability to contamination (Busenberg and Plummer 1992;Cook et al 1995;Goody et al 2006;Mahlknecht et al 2006b;Horst et al 2008;Darling et al 2012).…”
Section: Introductionmentioning
confidence: 99%